Kualitas Pelayanan Publik pada Bus Trans Jatim Koridor II Rute Mojokerto-Surabaya - Azeria Diazpitaloka Putri Sulistyono; Meirinawati Meirinawati; Eva Hany Fanida; Trenda Aktiva Oktariyanda (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
Public transportation plays an important role in supporting community mobility and accelerating regional economic growth. To improve public transportation services in East Java, the East Java Provincial Transportation Agency introduced the Trans Jatim Bus system. However, its implementation still faces several challenges, including long bus arrival times, the use of mobile applications that are difficult for elderly users, and inconsistencies in the availability of supporting facilities such as seating and trash bins at bus stops. This study aims to analyze the quality of Trans Jatim Bus services based on the service quality dimensions proposed by Wirtz and Lovelock. The research employs a descriptive qualitative approach. Data were collected through interviews, observations, and documentation, and analyzed using stages of data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that reliability has not met service standards due to prolonged waiting times. Responsiveness and assurance were found to meet service standards, as passengers expressed satisfaction with service responses and complaint handling. Empathy was considered adequate, although accessibility issues for elderly passengers remain. Tangible aspects were also sufficiently met, but inconsistencies were found in the provision of seating and trash bins at several bus stops. Based on these findings, the study recommends increasing the number of buses on corridor 2, evaluating bus schedules, conducting public awareness campaigns, and ensuring the consistent provision of seating and trash bins at all bus stops to improve overall service quality.